Angiotensin-Converting Enzyme 2 Deficiency Aggravates Glucose Intolerance via Impairment of Islet Microvascular Density in Mice with High-Fat Diet - Li Yuan; Ying Wang; Chunli Lu; Xiaoya Li (Journal of Diabetes Research)
The aim of this study was to evaluate the effects of angiotensin-converting enzyme 2 (ACE2) on glucose homeostasis and islet function in mice. Male wildtype (WT) and ACE2 knockout (ACE2 KO) mice were divided into chow diet group and long-term high-fat diet (HFD) group. After 16 weeks of feeding, the islet function of the animals was evaluated by intraperitoneal glucose tolerance test (IPGTT) and intraperitoneal insulin releasing test (IPIRT). The pancreas was immunohistochemically stained to analyze the relative content of insulin (IRC), vascular endothelial growth factor (VEGF), and microvessel density (MVD) in islets. There was no difference of body weight, area under curve of glucose (AUCG), area under curve of insulin from 0 to 5 min (AUGI0–5), MVD, and RVC (relative content of VEGF) between WT and ACE2 KO mice with regular chow diet. Under the condition of long-term HFD, the AUCG of ACE2 KO mice was increased obviously in comparison with the WT mice, with decreased IRC, MVD, AUGI0–5, AUCI0–30, and RVC (all P<0.05). In conclusion, these results show that ACE2 deficiency deteriorates islet function of mice with long-term HFD via impairment of islet microvasculature.